Wettbewerbsfähigkeit von Start-ups Erfolgreiche Düsseldorfer Unternehmen - Lutz, Eva; Süß, Stefan (De Gruyter, 2020)
This book details the development of ten successful start-ups, from initial founding to market success. It places a particular focus on the decisions made by the founders, as well as the factors influencing business performance. The ten case studies contained in this volume highlight the diversity and dynamism of Düsseldorf's start-up scene.